Profiling Local Business Enterprises and Direct Effect of Tourism in Villages of Muntei, Madobag and Matotonan, South Siberut, Mentawai, Indonesia - Rahmanita, Myrza; Asmaniati, Fetty; Dewi, Triana Rosalina (Institut Pariwisata Trisakti, 2020)
Mentawai is well known as an ecotourism area in Indonesia, with its Siberut National Park recognized as part of the World Network of Biosphere Reserves. People come to visit this exotic area every year to do activities and enjoying the natural surroundings. Tourist visits to Mentawai were escalating by years, both domestic and foreign tourists. Regional income from tourism was also increasing. Ecotourism is known worldwide for its benefit for economic contribution to local communities and poverty alleviation. The economic contribution of ecotourism is often appreciated through its direct effect on local business enterprises on sites. However, statistics today showed that Mentawai are still categorized as underdeveloped and poor. Therefore, this descriptive research objective was to assess tourism contribution by means of direct effect to local business enterprises and challenges faced by villages near Siberut National Park, South Siberut, Mentawai. A survey was conducted in November 2018 by distributing questionnaires to 19 representatives of tourism-related Local Business Enterprises (LBEs) using an accidental sampling technique. Data collected were then processed, analyzed and interpreted. In conclusion, this study shows that there is a low direct effect of tourism to the existing Local Business Enterprise in the villages of Muntei, Madobag, and Matotonan of South Siberut, Mentawai Island Regency, West Sumatera, Indonesia. In addition, essential challenges exist, not to mention managerial, predominantly concerning financial and legal matters. It is recommended that local government and other stakeholders put more consideration not only on environmental and social aspects, but also economy, represented by local business enterprises. Initiatives and integrated actions should be arranged and put in practice as empowering tourism, particularly ecotourism to its optimum, to bring about foremost contribution to local economy through direct effect of tourism to local business enterprises. Keywords: Tourism contribution, Direct effect of tourism, Local Business Enterprise, Ecotourism, Mentawai